2017
DOI: 10.17645/up.v2i4.1276
|View full text |Cite
|
Sign up to set email alerts
|

Suburban Innovations

Abstract: This commentary addresses the evolution of the North American suburb over the last 70 years, a period over which it adopted a development pattern marking a radical break from prior forms of urban settlement. Early in this period, the emerging suburban form constituted perhaps the sharpest transition in the history of urbanism in terms of urban form and transportation. This suburban form rapidly came to dominate North American metropolitan regions and spread to other parts of the world. In this commentary, I pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Other scholars have demonstrated that Canadian suburban development exhibits the characteristics of a path-dependent process. 18 This article considers whether and how CPAC may have been a central institution that contributed to that path-dependency. In order to demonstrate that this is what occurred in the suburbanization of Canada, the research team looked for evidence in the primary source materials that solidifies the present hypothesis that the strategic partnership between the government, corporate developers and large-scale builders, with the intent of boosting Canadian consumerism and, subsequently, its economy in the post-war years created sets of enduring institutions and community planning approaches that have had continuing impacts upon the processes and patterns of suburbanization in Canada.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Other scholars have demonstrated that Canadian suburban development exhibits the characteristics of a path-dependent process. 18 This article considers whether and how CPAC may have been a central institution that contributed to that path-dependency. In order to demonstrate that this is what occurred in the suburbanization of Canada, the research team looked for evidence in the primary source materials that solidifies the present hypothesis that the strategic partnership between the government, corporate developers and large-scale builders, with the intent of boosting Canadian consumerism and, subsequently, its economy in the post-war years created sets of enduring institutions and community planning approaches that have had continuing impacts upon the processes and patterns of suburbanization in Canada.…”
Section: Theoretical Frameworkmentioning
confidence: 99%